Application of Physical Gas Absorbers in Manipulating the CO2 Pressure of Kimchi Package. Issue 12 (12th November 2018) - Jaisan, Chalalai; An, Duck Soon; Lee, Dong Sun
Abstract : Abstract: Physical gas absorption and release of activated carbon or zeolite were used to attain the desired CO2 concentration profile inside a package of kimchi for its dynamic storage and consumption environment. The CO2 adsorption/desorption behavior of different combinations of physical scavengers in the microporous Tyvek sachet was measured at 0, 10 and 20 °C. A combination of highly permeable microporous Tyvek and much less permeable nylon/polyethylene laminate was also examined as a variable to help control the access of CO2 to the physical CO2 absorber. The composition of the absorber and its packing density in the sachet affected the CO2 absorption rate and capacity. Increased zeolite in the Tyvek sachet showed higher CO2 absorption followed by higher CO2 release concomitant with moisture sorption, while activated carbon itself had low CO2 absorption and little subsequent CO2 desorption. Lower temperatures increased the capacity of CO2 absorption and release along with lower CO2 absorption and release rates. A reduction in Tyvek area could decrease the absorption and release rates. An application of a physical CO2 absorber to the kimchi package was tested at 10 °C to show potential for keeping the desired CO2 pressure profile for carbonic cool flavor under tolerable pressure during storage and use. Practical Applications: Physical carbon dioxide absorbers consisting of zeolite and activated carbon inside the gas‐permeable sachet can be placed in kimchi packages for time‐dependent absorption and release of carbon dioxide, which responds in harmony with the fermentation profile of kimchi . Its practical potential is both to provide a carbonic cool taste of the product and to avoid excessive overpressure in the package through its shelf life when used in kimchi packaging. Its intelligent use may resolve the problem of a dull kimchi taste, which occurs when incorporating calcium hydroxide as the chemical scavenger in the package.